Blowing the whistle on workplace corruption: the role of ethical leadership - Hechanova, Ma. Regina (Archīum Ateneo, 2020)
Purpose The purpose of this study is to provide a structural model of the role of ethical leadership on intent to whistle blow workplace corruption using the theory of planned behaviors. Design/methodology/approach The study used a mixed method, sequential design. Interviews were conducted in the first phase to identify corrupt practices and validate the salience of the variables in the study. The second phase administered surveys to test the hypotheses of the study. Structural equation modeling (SEM) was done to analyze structural relationships among variables. Findings SEM results showed an adequately fit model, indicating ethical leadership predicting organizational norms and controls. It also found that ethical leadership has indirect effect toward employees’ attitude toward corruption through organizational norms and control. Furthermore, ethical leadership also has indirect effect on intent to whistle blow through organizational controls. Research limitations/implications This study was conducted in the Philippines, a high-power distance culture. In such a culture, the influence of leadership is crucial, as it dictates standard behaviors of members and the organization as a whole. Future research may wish to explore whether the findings would also apply in low-power distance cultures. Practical implications The finding suggests that ethical leadership is crucial in shaping organizational norms and controls, which in turn, influences employees’ attitude toward corruption and their intention to whistle blow. Originality/value The study contributes to corruption literature by providing empirical evidence of the structure model how the role of ethical leadership shapes organizational norms and controls that, in turn, influences employee attitude toward corruption and intent to whistle blow.